APLIKASI BEYOND BUDGETING YANG DIDUKUNG “ARIMA” TIME SERIES MODELING DALAM MEMREDIKSI PENDAPATAN JASA UNTUK EFEKTIVITAS PENGENDALIAN MANAJEMEN PADA KONSULTAN ”SMC” SURABAYA - Wiyono Pontjoharyo (Jurnal Akuntansi Bisnis, 2017)
The rising pressure of competition put more demands to plan and control better as well as delivering the right quality of products and services. Therefore, the implementation of management control systems through budgeting should be one of the best solutions for business effectiveness, moreover for the long run, the business sustainability. The application of beyond budgeting by using the ARIMA time series modeling is the most appropriate and reliable result in revenue planning for the effectiveness of management control systems in SMC consulting firm, as the local business potential to exist in coming tougher competition. This study reveals that the right design of beyond budgeting will enhance the SMC to perform better from the traditional incremental budgeting. It is because the beyond budgeting provides the broader freedom to be creative in reaching the best effort of the human resources involved, under the appropriate support of information technology and the well implemented of result control in management control system. By having a better controlled performance through the developing of beyond budgeting process should preserve the business sustainability to be contributed into national competitive advantage. Key words: management control systems, beyond budgeting, ARIMA (Autoregressive Integrated Moving Average) time series modeling, business sustainability